2007
DOI: 10.1080/02773810701700802
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Optical Brightening Agents (OBA) and their Brightening Efficiency on HYP‐Containing Paper Sheets

Abstract: Optical brightening agents (OBA) or fluorescent whitening agents (FWA) are commonly used in the paper industry to improve the optical performance of paper products. The increased use of bleached chemi-thermo-mechanical pulp (BCTMP) or high-yield pulp (HYP) in printing and writing paper grades has initiated research topics on the brightening efficiency of OBA on mechanical pulp-containing furnishes. In this study, process parameters that may affect the retention of OBA were investigated, such as furnish composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 1 publication
1
34
0
1
Order By: Relevance
“…Ou seja, o alvejante aumenta o comprimento de onda da radiação UV incidente refletindo-a como radiação visível. mais eficiente é o tratamento com alvejante (ZHANG et al, 2007b). Quanto ao tipo de polpa, os alvejantes têm menos afinidade às polpas de alto rendimento do que à polpa química (ZHANG et al, 2007b).…”
Section: Introductionunclassified
“…Ou seja, o alvejante aumenta o comprimento de onda da radiação UV incidente refletindo-a como radiação visível. mais eficiente é o tratamento com alvejante (ZHANG et al, 2007b). Quanto ao tipo de polpa, os alvejantes têm menos afinidade às polpas de alto rendimento do que à polpa química (ZHANG et al, 2007b).…”
Section: Introductionunclassified
“…[6,[10][11] An earlier study showed that the OBA brightening process can be conveniently incorporated into the alkaline peroxide bleaching process. [12] This approach has several advantages over the conventional method, whereby, OBA is added in the wet end of the papermaking process.…”
mentioning
confidence: 99%
“…The presence of cations such as Ca 2+ in the white water can increase the OBA retention. Also, a higher temperature and longer time of OBA with pulp fibers improved the OBA retention [11].…”
Section: Significantmentioning
confidence: 93%
“…It has been reported that the brightening efficiency of OBA is determined by its retention and effectiveness on pulp fibers [9,10]. The retention of OBA is affected by the types of OBA, fixing agents, temperature and contact time [11]. The presence of cations such as Ca 2+ in the white water can increase the OBA retention.…”
Section: Significantmentioning
confidence: 99%